Indonesian Translation and Appropriation of the Works of Shariati and Hanafi in the New Order’s Islamic Discourses - Mujiburrahman, Mujiburrahman (Studia Islamika, 2018)
This paper discusses the discourses of Indonesian Muslim intellectuals on the works of Ali Shariati and Hassan Hanafi in Indonesia’s New Order. The literature discussed here consists primarily of the articles written by prominent Indonesian Muslim intellectuals, and most of the articles were introductions to the translated books of Shariati and Hanafi. The articles shows us that Shariati’s and Hanafi’s ideas were received, interpreted, criticized, and appropriated by the intellectuals in order to make them relevant to the Indonesian context.The idealization of Shariati as an intellectual, a more open attitude towards Shi’ism, and the discussion of his socialist tendencies could not be separated from the demands of the Indonesian political situation during the New Order. Likewise, Hanafi’s ideas on the relation between religion, ideology and development, and the Islamic Left and Occidentalism found their relevance to the Indonesian socio-political context.Therefore, the discourses are elements of the New Order’s Islamic discourses.DOI: 10.15408/sdi.v25i2.7181